THE RELATIONSHIP BETWEEN FAMILY SUPPORT AND QUALITY OF LIFE OF STROKE PATIENTS IN THE OUTPATIENT INSTALLATION OF THE ROYAL PROGRESS HOSPITAL NORTH JAKARTA. - Zuriati; Suriya, Melti; Putri, Noor Lusty; Prastiwi, Ikha; Pratiwi, Dilia Ananda; Yazid, Hauzan; putri, Cindy grasella; Agustin, Ami Tazkia; Fitriyani, Liana; andhini, Nindya (Proceeding of International Conference on Multidisciplinary Research, 2024)
Stroke is the second leading cause of death and the third leading cause of disability worldwide. Sudden changes in life for stroke patients impact their psychological conditions, with physical limitations that can interfere with the quality of life of post-stroke patients. Family support is crucial in helping post-stroke patients achieve an optimal life. The purpose of this study was to determine the relationship between family support and the quality of life of post-stroke patients. This study is a quantitative analytical correlational study with a cross-sectional approach involving 73 respondents selected through a purposive sampling technique. Bivariate analysis was conducted using the Chi-Square test. The results of the univariate analysis showed that the quality of life of post-stroke patients was good in 53.7% of cases, and family support was good in 56.2% of cases. Bivariate analysis obtained a p-value of 0.000, indicating a relationship between family support and the quality of life of post-stroke patients. It is hoped that nurses can prepare the families of post-stroke patients with discharge planning before they return home and conduct home visits so that families can care for patients well, prevent stroke recurrence, and improve the quality of life, especially in the physical and psychological domains post-stroke.